Biflavones and megastigmane glycosides from the leaves of Antidesma bunius - Trang, Do Thi; Huyen, Le Thi; Thuy Hang, Dan Thi; Nhiem, Nguyen Xuan; Yen, Pham Hai; Tai, Bui Huu; Tuan Anh, Hoang Le; Minh, Chau Van; Kiem, Phan Van (Vietnam Journal of Chemistry, 2016)
Two biflavones, podocarpusflavone A (1) and amentoflavone (2) and two megastigmane glycosides, byzantionoside B (3) and (6S,9R)-roseoside (4) were isolated from the methanol extract of the leaves of Antidesma bunius. Their structures were determined by spectroscopic methods and in comparison with the published data. Keywords. Antidesma bunius, Euphorbiaceae, biflavone, megastigmane.